Związki frazeologiczne i skrzydlate słowa wywodzące się z filmów w reżyserii Stanisława Barei (na wybranych przykładach) - Połowniak-Wawrzonek, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
In contemporary Polish, there are phrases and winged words that come from films, TV series, songs, the language of politics, advertising, popular TV and radio programmes. Among the well-established expressions from the film and TV series, there are permanent verbal connections derived from the films by S. Bareja. Fixed verbal connections stand out among them: Słuszną linię ma nasza władza, Jak jest zima, to musi być zimno, Narodziła się nowa świecka tradycja, Ile jest cukru w cukrze, Nie wiem, nie znam się, nie orientuję się, zarobiony jestem. These idioms, winged words appear in both canonical and modified form. The usual modifications change or replace parts of the original phrases. Innovation strengthens the invariant. Fixed verbal connections of this type are usually ironic and comic. They often fulfill a ludic or phatic function – their appearance is the sender’s communicative signal addressed to the recipient participating in the same culture which is being created today not only by literature, music, painting and other works of art, but also by films, TV series, television and radio programs and so on.